2006
DOI: 10.1111/j.1532-849x.2006.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Die Spacer on Retention and Fitting of Complete Cast Crowns

Abstract: Increasing the area of the die surface covered with spacer improved the fit of the cast restoration. After cementation, the resin modified glass ionomer showed better adaptation; however, the optical microscopy and scanning microscopy correlate well. Resin cement had the highest resistance to tensile forces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
(54 reference statements)
3
28
0
3
Order By: Relevance
“…Olivera AB et al, have carried out a study to evaluate the effect of application of die spacer on fit and retention of complete cast crowns by using optical microscope and scanning electron microscope on different areas of stone dies i.e., Occlusal and 1/3 of axial surfaces , occlusal and 2/3 of axial surfaces & entire preparation down to 0.5mm short of the margin and concluded that fit of the cast restorations can be improved by increasing the surface area of application of the die spacer on the entire preparation down to 0.5mm short of the margin [13].…”
Section: Discussionmentioning
confidence: 99%
“…Olivera AB et al, have carried out a study to evaluate the effect of application of die spacer on fit and retention of complete cast crowns by using optical microscope and scanning electron microscope on different areas of stone dies i.e., Occlusal and 1/3 of axial surfaces , occlusal and 2/3 of axial surfaces & entire preparation down to 0.5mm short of the margin and concluded that fit of the cast restorations can be improved by increasing the surface area of application of the die spacer on the entire preparation down to 0.5mm short of the margin [13].…”
Section: Discussionmentioning
confidence: 99%
“…4) (Olivera en Saito, 2006). Ook wordt van de approximale contactvlakken van de buurelementen ongeveer 0,1 mm afgenomen om later in de klinische situatie stevige interdentale contacten te verkrijgen.…”
Section: Analoogunclassified
“…These techniques may give misleading results because distortions are possible at any stage. 7,8,12,33,[47][48][49][50][51][52] For standardization of copings, some authors preferred to use standard burnout caps fabricated by the implant manufacturer. 8,13,15,33,47,51 However, investing and casting procedures probably contribute similarly to distortion.…”
mentioning
confidence: 99%